DEVELOPING A WELL-BEING MODEL FOR GASTRONOMIC TOURISM ENTRE-PRENEURS USING A EUDAIMONIC DIMENSION APPROACH - Edouard Aryadi Supriyadi (International Journal of Social Science, 2026)
Gastronomic tourism has rapidly developed as a subsector of tourism that not only offers culinary experiences but also represents local cultural iden- tity. However, gastronomic entrepreneurs face complex challenges ranging from intense competition to external pressures, which affect their well-being. This study aimed to develop a well-being model based on the eudaimonic di- mension for gastronomic tourism entrepreneurs through a case study of Hardadi, the owner of Singkong Keju D-9 in Salatiga. The research employed a qualitative approach with phenomenological methods, using in-depth inter- views, participatory observation, and documentation, analyzed through the- matic analysis with the support of NVivo software. The findings revealed nine core components of eudaimonic well-being: generosity, sincerity, self- introspection, spirituality, inner peace, usefulness to others, gratitude, humil- ity, and optimism. These components demonstrate that entrepreneurs’ well- being is not solely determined by economic factors but also by life meaning, social relationships, and spiritual values. The conceptual model developed in this study shows that eudaimonic well-being functions in two ways: as an out- come of entrepreneurial activity and as psychological capital to face business challenges. The findings provide practical implications for entrepreneurs in in- tegrating meaningful well-being into business practices, academics in enriching studies on the relationship between well-being and entrepreneurship, and poli- cymakers in designing programs that support the sustainability of gastronomic tourism in Indonesia.